Barnes-Ismagilov Integrals and Hypergeometric Functions of the Complex Field - Neretin, Yury A. (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We examine a family ₚᶜq[⁽ᵃ⁾₍b₎; ] of integrals of Mellin-Barnes type over the space ℤ × ℝ, such that functions naturally arise in the representation theory of the Lorentz group. We express ₚᶜq() as quadratic expressions in the generalized hypergeometric functions ₚFq₋₁ and discuss further properties of the functions ₚᶜq().